Increased Bone Marrow Adiposity in a Context of Energy Deficit: The Tip of the Iceberg? - Ghali, Olfa; Al Rassy, Nathalie; Hardouin, Pierre; Chauveau, Christophe (Frontiers in Endocrinology, 2016)
Elevated bone marrow adiposity is defined as an increase in the proportion of the bone marrow cavity volume occupied by adipocytes. This can be caused by an increase in the size and/or number of adipocytes. Bone marrow adiposity increases with age in a bone-site-specific manner. This increase may be linked to certain pathophysiological situations. Osteoporosis or compromised bone quality is frequently associated with high bone marrow adiposity. The involvement of bone marrow adipocytes in bone loss may be due to commitment of mesenchymal stem cells to the adipogenic pathway rather than the osteogenic pathway. However, adipocytes may also act on their microenvironment by secreting factors with harmful effects for the bone health. Here, we review evidence that in a context of energy deficit (such as anorexia nervosa and restriction rodent models) bone alterations can occur in the absence of an increase in bone marrow adiposity. In severe cases, bone alterations are even associated with gelatinous bone marrow transformation. The relationship between bone marrow adiposity and energy deficit, and the potential regulators of this adiposity in this context are also discussed. On the basis of clinical studies and preliminary results on animal model we propose that competition between differentiation into osteoblasts and differentiation into adipocytes might trigger bone loss at least in moderate-to severe anorexia nervosa and in some calorie restriction models. Finally, some of the main questions resulting from this hypothesis are discussed.